Leadership Behaviors in Islam: Integrating Managerial Leadership and Servant Leadership - Mahazan Abdul Mutalib @ Talib; Wan Mohd Fazrul Azdi Wan Razali; H. Siti Aishah; Yuseri Ahmad; Mohd Rosmizi Abd Rahman; K. Muhammad Yusuf; Mohd Rumaizuddin Ghazali (IDOSI Publications, 2024)
The purpose of this research is to reinvestigate the 19 themes and its items of Islamic Leadership Inventory (ILI) developed to measure Islamic Leadership behaviors. The major focus of this research is to strengthen the Islamic theoretical supports of ILI by conducting Content Analysis procedures on the four categories of texts namely 1) The Quran and Ahadiths, 2) Classical literature of Islam, 3) Modern literature of Islam and 4) The literature of conventional leadership. Three steps were applied to conduct the Content Analysis. First, items consisting Islamic leadership behaviors were extracted from the Quran and Ahadiths. Secondly, items consisting the same focus (Islamic Leadership) were extracted from the classical and modern texts of Islamic literature. The items were fitted in the Islamic Leadership themes developed from the first procedure. Third, the existing themes and items of original ILI were compared and integrated with the new established themes and items. Based on the three procedures, this research expanded the 19 themes of original ILI into a newly identified 25 Islamic Leadership themes. Items of original ILI were also modified to represent the 25 new themes. Specific description of Islamic leadership behaviors were found in the Quran, Ahadiths and Islamic literature. This research transformed the leadership description into a set of measurable Islamic Leadership behaviour items. In sum, this research found the existing ILI themes and items fitted well in the newly identified 25 Islamic Leadership themes. Furthermore, the themes are consistent with the Maqasid al- Syariah. This has suggested the 25 themes are foundational and should be considered as stable acts to describe effective Islamic Leadership behaviors.